Thermo-mechanical properties of the gypsum composites reinforced with natural and recycled fibers - Amna Iqbal; Sajjad Mubin; Ahmad Riaz; Rehan Masood; Ahmed Iqbal (Journal of Asian Architecture and Building Engineering, 2025)
The demand for environmentally friendly substitutes that can improve the performance of traditional building materials has prompted studies into these eco-friendly alternatives. With an emphasis on their potential to enhance thermal performance and advance environmental sustainability, this study examines the thermo-mechanical characteristics of gypsum composites reinforced with natural and recycled fibers. Banana stem fiber and apparel waste were incorporated in 2.5–7.5% weightage into the gypsum matrix to evaluate their influence on physical, thermal, and mechanical properties. During experimentation, samples of gypsum composite with different kinds and contents of fibers were created. Thermal conductivity, compressive strength, flexural strength, and physical properties, including bulk density and water absorption, were measured. The outcomes showed that the tensile strength, flexibility, and thermal resistance of the gypsum composites were all greatly improved by the addition of both natural and recycled fibers. In terms of insulation materials, banana fiber composites outperformed recycled fiber composites, with an improvement of 87% thermal performance in comparison to the control samples. In particular, the value of thermal conductivity for control sample, with no fiber addition, was 0.412, while it was reduced to 0.0507 W/mK in case of 7.5% natural fiber addition. Furthermore, incorporating recycled fibers reduced waste, which is consistent with the circular economy concepts in the building industry. The study emphasizes the fiber-reinforced gypsum composites’ potential as an environmentally friendly and highly effective building material as a more environmentally friendly substitute for conventional gypsum-based products.